filmov
tv
If the roots of (b-c)x2+(c-a)x+(a-b) = 0 are real and equal than which of the following is true:a)
Показать описание
If the roots of (b-c)x2+(c-a)x+(a-b) = 0 are real and equal than which of the following is true:
a) 2b=a+c
b) 2a=b+c
c) 2c=a+b
d) 2b=a-c
Telegram Link Class 10
a) 2b=a+c
b) 2a=b+c
c) 2c=a+b
d) 2b=a-c
Telegram Link Class 10
If the roots of the equation (a-b)x^2+(b-c)x+(c-a)=0 are equal prove that 2a=b+c
If the roots of the equation (b-c)x^2+(c-a)x+(a-b)=0 are equal, then prove that 2b=a+c.
If the roots of the equation (b-c)x2+(c-a)x+a-b=0 are equal then prove that 2b = a+c
If the roots of the equation (b−c)x2+(c−a)x+(a−b)=0 are equal, then prove that 2b=a+c
If the roots of (b-c)x2+(c-a)x+(a-b) = 0 are real and equal than which of the following is true:a)
If roots equation (b-c)x² + (c-a)x + (a-b) = 0 are equal then Prove 2b = a + c
If the roots of the equation ax^2+cx+c=0 be in the ratio m:n,prove that,√m/n+√n/m+√c/a=0
If the roots of the equation (a-b)x^2 + (b-c)x + (c-a) = 0 are equal, then prove that 2a = b + c.
If the roots of (c^2-ab) x^2-2(a^2-bc)x+(b^2-ac)=0 are equal, show that a=0 or (a^3+b^3+c^3 )=3abc.
If \( a, b, c \in Q \), then roots of the equation \( (b+c-2 a) x^{...
If the roots of the equation (b-c)x2+(c-a)x+(a-b)=0 are equal, then prove that 2b=a+c.....
If one of the roots of the equation then `a(b-c) x^2 + b(c-a) x + c (a-b) = 0` is what is th...
7. If a,b,c rational and a + b + c=0, show roots of (b+c–a)x² + (c+a–b)x +(a+b+c) = 0 are rational....
How To Find The Sum and Product of the Roots of a Quadratic Equation - Algebra
If the roots of the equation `(b-c)x^2+(c-a)x+(a-b)=0` are equal then `a,b,c` will be in
If the roots of (b-c)x2+(c-a)x+(a-b) = 0 are real and equal than which of the following is true:a)
Q24 If the roots of the equation (a-b)x²+(b-c)x+(c-a)=0 are equal then prove that 2a=b+c
If the roots of the equation (c^2-ab)x^2-2(a^2-bc) x+b^2-ac=0 are equal, prove that either a=0...
If the roots of ax^2+bx+c=0 be in the ratio 3:4 prove that, 12b^2=49ac
If roots of the equation(b-c)x²+(c-a)x+(a-b)=0 are equal, then prove that 2b=a+c|@Sk Wonder Kids.
The roots of the equation `ax^2+bx + c = 0` will be imaginary if, A)`a gt 0 b=0 c lt 0` B) `a ...
If coefficients of the equation `ax^2 + bx + c = 0` , `a!=0` are real and roots of the equatio...
If the roots of the equation (a2+b2)x2-2(ac+bd)x+(c2+d2)=0 are equal prove that a/b=c/d
'If the roots of the equation `(x^2-b x)/(a x-c)=(m-1)/(m+1)` are equal to opposite sign, then...
Комментарии